Relación entre el grado de instrucción y el nivel de conocimiento en las madres de familia sobre alimentación infantil saludable - Chávez Ascoy, María Goretti (2023)
Infant feeding is considered of global importance, due to the malnutrition numbers that cause half of the deaths in children under 5 years of age, and excessive weight gain, which represents the fifth cause of global mortality. At the level of La Libertad Region, chronic malnutrition and overweight-obesity affect the child population, exceeding the national average, so the objective was to determine the relationship between the level of education and the level of knowledge about the infant feeding in mothers of the urban area of Santiago de Chuco, year 2016. The investigation was descriptive, basic and correlational design with a sample of 260 mothers with children under 6 years of age, randomly selected. The results identified that the majority of mothers had secondary (38.4%) and primary education (35.8%), followed by illiteracy (16.2%); the majority had a medium level of knowledge about healthy feeding (51.2%), followed by a high level (31.9%) and a low level (16.9%); when evaluating the relationship between the variables, it is established that the majority of women with a high level of knowledge (84%) had a higher level of education, and of the women with a low level of knowledge, 23.8% were illiterate, finding a very significant statistical relationship (p<0.001). Concluding, there is a very significant statistical relationship between the level of education and the level of knowledge of mothers about healthy infant feeding.